2020
DOI: 10.20493/birtop.726411
|View full text |Cite
|
Sign up to set email alerts
|

Salgin Hastalik Dönemi̇nde Algilanan Sosyal Desteği̇n Bi̇reyleri̇n Psi̇koloji̇k Sağlamliği Üzeri̇ndeki̇ Etki̇si̇ni̇n İncelenmesi̇

Abstract: Bu çalışma salgın hastalık döneminde algılanan sosyal desteğin bireylerin psikolojik sağlamlığı üzerindeki etkisini belirlemek amacıyla yapılmıştır. Araştırma, nicel araştırma desenlerinden ilişkisel tarama modeli benimsenerek yürütülmüştür. Araştırmanın çalışma grubunu farklı demografik yapıya sahip 350 kişi oluşturmaktadır. Araştırmaya katılan bireyler kolay ulaşılabilir örnekleme yöntemiyle belirlenmiştir. Çalışma Dünya Sağlık Örgütünün pandemi ilan ettiği 2020 Mart ayında yürütülmüştür. Araştırmada veri to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…In some of the previous studies, as in our research, it has been observed that men have higher resilience than women (Açıkgöz, 2016;Aydın, Öncü, Akbulut, & Küçükkılıç, 2019;Deniz et al, 2020;Erkoç & Danış , 2020;Karakış, 2019;Kımter, 2020;Sezgin, 2016;Taşkın et al, 2017;Yazıcı-Çelebi, 2020;), and in some, women than men (Atan & Ünver, 2019;Çutuk, Beyleroğlu , Hazar, Akkuş Çutuk, & Bezci, 2017;Durmuş & Okanlı, 2018;Kılıç 2014;Koç Yıldırım, Yıldırım, Otrar, and Şirin, 2015;Oktan, Odacı, and Berber-Çelik 2014;Özden, 2015;Tonbül, 2020). There are also studies showing that there is no difference in resilience level by gender (Akça, 2012;Alkım, Arı et al, 2020;Aydın, 2010;Aydın & Egemberdiyeva, 2018;Aydoğdu, 2013;Bektaş & Özben, 2016;Bolat 2013;Can & Cantez, 2018;Dursun & Özkan, 2019;Fingerless, 2019;Işık, & Çelik, 2020;Karal & Biçer, 2020;Karaırmak, & Güloğlu, 2014;Özer, 2013;Özkapu, 2019;Yıldız-Türker, 2018). The reason for the lower level of resilience of women is shown to be that women have more roles in society compared to men, this situation brings more difficulties for them and women to have a more emotional structure (Aydın, Öncü, Akbulut, & Küçükkılıç, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In some of the previous studies, as in our research, it has been observed that men have higher resilience than women (Açıkgöz, 2016;Aydın, Öncü, Akbulut, & Küçükkılıç, 2019;Deniz et al, 2020;Erkoç & Danış , 2020;Karakış, 2019;Kımter, 2020;Sezgin, 2016;Taşkın et al, 2017;Yazıcı-Çelebi, 2020;), and in some, women than men (Atan & Ünver, 2019;Çutuk, Beyleroğlu , Hazar, Akkuş Çutuk, & Bezci, 2017;Durmuş & Okanlı, 2018;Kılıç 2014;Koç Yıldırım, Yıldırım, Otrar, and Şirin, 2015;Oktan, Odacı, and Berber-Çelik 2014;Özden, 2015;Tonbül, 2020). There are also studies showing that there is no difference in resilience level by gender (Akça, 2012;Alkım, Arı et al, 2020;Aydın, 2010;Aydın & Egemberdiyeva, 2018;Aydoğdu, 2013;Bektaş & Özben, 2016;Bolat 2013;Can & Cantez, 2018;Dursun & Özkan, 2019;Fingerless, 2019;Işık, & Çelik, 2020;Karal & Biçer, 2020;Karaırmak, & Güloğlu, 2014;Özer, 2013;Özkapu, 2019;Yıldız-Türker, 2018). The reason for the lower level of resilience of women is shown to be that women have more roles in society compared to men, this situation brings more difficulties for them and women to have a more emotional structure (Aydın, Öncü, Akbulut, & Küçükkılıç, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Dolayısıyla tek ebeveyn annelerin hayatlarındaki yeni ve zorlu durumlara karşı bilişsel esneklik becerilerini sergilemelerinde eğitim durumlarının etkisiz kaldığı düşünülmektedir. Alan yazına göre, psikolojik sağlamlığın eğitim durumuna dayalı olarak anlamlı bir farklılık Hatice ODACI, Emine ÜLKEN, Kenan BÜLBÜL göstermediğini bulgulayan (Parmaksız, 2019;Karal ve Biçer, 2020;Kımter, 2020) çalışmalar olduğu gibi, farklılaştığını bulgulayan (Ersoy ve Gülbüz, 2020) çalışmalar da vardır. Bu konuda alan yazında bir tutarlılık olmamakla birlikte mevcut sonucun psikolojik sağlamlığı etkileyebilecek farklı kaynakların varlığıyla ilişkili olabileceği düşünülmektedir.…”
Section: Discussionunclassified
“…20 Perceived social support from family, friends, and other notable people is closely related to the level of resilience. 21 It has been found that the COVID-19 event has a significant effect on perceived social support and its dimensions. As the impact of the COVID-19 event increases, the social support perceived by dentists increases.…”
Section: Discussionmentioning
confidence: 99%